Determination of tafenoquine in dried blood spots and plasma using LC and fluorescence detection - Susanne Römsing (2018)
Background: The growing problem of parasites developing resistance to the traditional antimalarial drugs makes the development of new effective and safe drugs crucial. Tafenoquine is a new promising antimalarial drug for prophylaxis and treatment. Results: A bioanalytical method for the determination of tafenoquine in 100 l of capillary blood applied onto sampling paper and in 100 l of plasma has been developed and validated. The Whatman 31 ET Chr paper was treated with 0.6 mol/l tartaric acid to improve the extraction recovery and solid-phase extraction was used for cleanup procedure of the blood samples. Plasma samples were precipitated with methanol. Tafenoquine and internal standard were separated on a Zorbax SB-CN column by reversed-phase LC and detected with fluorescence detection at 262 and 470 nm. The within- and between-day variations were below 10 and 14%, respectively, over the range 50-200 nmol/l for capillary blood on sampling paper and below 6 and 10% for plasma samples. The LLOQ of the method was 50 nmol/l. Conclusion: The developed method has adequate sensitivity and is highly suitable for clinical studies in dried blood spots and plasma. © 2011 Future Science Ltd.